TiO2-based wave-absorbing ceramic taking Yb2Si2O7 as matrix and preparation method of TiO2-based wave-absorbing ceramic
By introducing TiO2 into the Yb2Si2O7 matrix absorbing material and using PIP process to form nano YbSiOTi composite ceramics, the problem of insufficient electromagnetic wave absorption capacity of existing absorbing materials in harsh environments is solved, and high-efficiency electromagnetic wave absorption and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411861208.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
AI Technical Summary
The existing absorbing materials have low electromagnetic wave absorption strength and low effective absorption frequency band in harsh environments. The research and development of traditional absorbing materials is in a bottleneck period, which cannot meet the high requirements for absorbing materials in harsh environments.
Using Yb2Si2O7 as the matrix, TiO2 is introduced as an absorber and polymer impregnation and cracking (PIP) technology is used to form nano YbSiOTi complex phase absorbing ceramics with spherical TiO2 to enhance its electromagnetic wave absorption performance.
It significantly improves the electromagnetic wave absorption performance, can effectively absorb electromagnetic waves in harsh environments, and has good oxidation and corrosion resistance.
Smart Images

Figure HDA0005193243930000011 
Figure HDA0005193243930000012 
Figure HDA0005193243930000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of absorbing materials, and in particular relates to a TiO2-based absorbing ceramic with Yb2Si2O7 as a matrix and a preparation method thereof. Background Art
[0002] At present, the rapid development of wireless communications and the increasing popularity of smart homes, transportation and medical equipment have brought convenience to today's fast-paced society. At the same time, a large number of electronic devices have also greatly increased electromagnetic radiation, causing serious electromagnetic pollution problems. These electromagnetic pollutions not only interfere with the operation of electrical equipment, but are also harmful to human health and the natural environment. For this reason, it is of great significance to develop high-performance electromagnetic wave absorbing materials that convert incident electromagnetic waves into heat or dissipate them through interfaces. Moreover, with the widespread application of absorbing materials in certain equipment, especially in high temperature and water-oxygen environments, higher requirements are put forward for strong absorption of electromagnetic waves in terms of anti-oxidation and corrosion resistance.
[0003] Rare earth silicates have low thermal expansion coefficient, good chemical stability and excellent corrosion resistance, and are the most promising environmental barrier coating materials for high-temperature silicon-based ceramics. Among them, Yb2Si2O7 is a typical high-temperature structural ceramic, which is widely used in high-temperature oxidation-resistant coatings, corrosion-resistant ceramics and heat-resistant shock coatings. It has strong environmental adaptability, but it also has the disadvantages of low absorption intensity and low effective absorption band. From the application point of view, it cannot be used as an absorption material. In addition, the research on absorption materials is still mainly focused on traditional absorption materials (traditional electromagnetic wave absorption ceramics are composed of absorbents and carriers), with little success.
[0004] In view of the current situation, the research team of this invention believes that it is necessary to change conventional thinking and not be limited by the research and development path of traditional absorbing materials. They develop a new type of microwave absorbing material that can be used in harsh environments to meet the high requirements of harsh environments on the absorbing performance, anti-oxidation and corrosion resistance of absorbing materials. Summary of the invention
[0005] Aiming at the high requirements on the performance of absorbing materials in harsh environments and the bottleneck period of the current research and development of traditional absorbing materials, the present invention provides a TiO2-based absorbing ceramic with Yb2Si2O7 as a matrix and a preparation method thereof.
[0006] The concept of the present invention:
[0007] The research team of the present invention believes that Yb2Si2O7 has strong environmental adaptability and is very suitable for harsh environments. However, due to its low absorption intensity and low effective absorption band, it has not been well applied in the field of absorption materials. The present invention attempts to further develop on the basis of Yb2Si2O7 ceramics in order to obtain an absorbing material that meets the requirements.
[0008] The research team of this invention conducted an in-depth analysis on the problems existing in Yb2Si2O7 ceramics and found that it is mainly because this type of ceramic matrix has a relatively high real part of the dielectric constant. A large amount of electromagnetic waves will be reflected on the surface of the material, and the electromagnetic waves cannot enter the interior of the material as much as possible to be absorbed. At the same time, due to the lack of an effective electromagnetic wave dissipation phase, its electromagnetic wave loss capacity is insufficient.
[0009] In view of the above factors, and the fact that traditional electromagnetic wave absorbing ceramics are composed of absorbents and carriers, the present invention intends to introduce an absorbent to overcome the problems currently faced by such ceramic matrices. TiO2 is a conductive semiconductor with excellent performance and is widely used. The research team of the present invention also selected TiO2 as an absorbent, and the method of introducing TiO2 and the form of TiO2 introduced are exactly what the present invention needs to consider.
[0010] In order to be applied in harsh environments and meet high requirements for anti-oxidation and corrosion resistance, the absorbent ceramic finally obtained by the present invention must have a dense microstructure, so as to reduce the diffusion channel of corrosive media (such as water, oxygen, etc.) inside the material as much as possible. In addition, the material should also have a certain complexity inside, so that electromagnetic waves can undergo multiple reflections, scattering, absorption and other processes inside the material, and the energy is fully lost. To this end, the present invention intends to introduce spherical TiO2 by polymer impregnation and cracking process.
[0011] To achieve the above purpose, the technical solution provided by the present invention is:
[0012] A method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix, which is special in that:
[0013] 1) Yb2Si2O7 powder and polyvinyl alcohol are uniformly mixed to obtain a mixture, and the mixture is pressed into a shape, and then sintered in an air atmosphere at a temperature of 1400-1600° C. for 2-3 hours to obtain a porous Yb2Si2O7 ceramic; the calcination temperature and time are controlled within the range, mainly because if the temperature deviates from the range, an impurity phase may be generated or the growth direction and integrity of the crystal may be affected, thereby affecting the performance of the ceramic, and insufficient calcination time will result in incomplete phase transformation and low crystallinity, affecting the crystal structure and physical properties of the ceramic;
[0014] 2) Under vacuum conditions, the porous Yb2Si2O7 ceramic obtained in step 1) is placed in a solution of isopropyl titanate or tetrabutyl titanate (C 16 H 36 O4Ti) solution for 30-60min (if the immersion time is too short, the introduction of Ti source in TiO2 may not fully penetrate into the interior of the ceramic, resulting in uneven distribution of active substances in the ceramic matrix), then placed in an oxygen-free environment at a temperature of 100-150°C for curing for 2-3h (i.e., the impregnated sample is placed in a suitable position in a heating furnace, the air in the furnace is exhausted, and the curing is carried out according to the curing temperature and time), and finally placed in an inert gas atmosphere for pyrolysis, so that the impregnated isopropyl titanate solution or tetrabutyl titanate is anaerobic pyrolyzed into TiO2; this The control of curing temperature and time is also very important. A lower temperature (below 100°C) will reduce the thermal motion speed of molecules in the solution, reduce the activity of the solution, and slow down the rate of penetration into the porous Yb2Si2O7 ceramic. Too high a temperature will cause the isopropyl titanate solution or tetrabutyl titanate to decompose or volatilize prematurely during the impregnation process, reducing the content of effective substances that can participate in the reaction. If the curing time is too short, it is impossible to form a sufficiently stable and complete chemical bond or microstructure. If the curing time is too long, the formed structure will overgrow or undergo some adverse changes.
[0015] 3) Repeat step 2) for 2-4 times to finally obtain TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix, namely, nano-YbSiOTi composite microwave absorbing ceramics.
[0016] Furthermore, in step 1), the mass fraction of Yb2Si2O7 powder in the mixture is 70-90%.
[0017] Furthermore, in step 2), the pyrolysis temperature is 1200-1500° C. and the time is 2-3 h.
[0018] Further, in step 1), the preparation method of Yb2Si2O7 powder is as follows:
[0019] Dissolve Yb(NO3)3·6H2O in deionized water to obtain solution A;
[0020] Dissolve ethyl orthosilicate in ethanol and stir to obtain solution B;
[0021] At room temperature, solution A and solution B are mixed and stirred to obtain a transparent gel C;
[0022] After drying gel C, it was calcined, cooled to room temperature, and ball-milled to obtain Yb2Si2O7 powder;
[0023] The drying process conditions are: first drying at 70-90°C for 20-30h, and then continuing drying at 110-150°C for 11-13h;
[0024] The process conditions for roasting are: roasting temperature is 1100°-1200°C, and roasting time is 2-4h;
[0025] The ball milling process is as follows: ball milling for 20-60 minutes, repeating this process 5-15 times with a time interval of 10-20 minutes, and obtaining Yb2Si2O7 powder with a particle size of 50-100 microns after drying.
[0026] Further, in step 1), the molar ratio of Yb(NO3)3 to ethyl orthosilicate is 1:1-1.5;
[0027] The concentration of Yb(NO3)3 in solution A is 3.5-5 mol / L, and the concentration of ethyl orthosilicate in solution B is 3.5-5 mol / L.
[0028] The present invention also provides a TiO2-based absorbing ceramic with Yb2Si2O7 as the matrix, which is special in that it is prepared by the above-mentioned preparation method. The nano YbSiOTi composite absorbing ceramic prepared by the method presents a special structure of lamellar and spherical composites under the microscopic view. Its special structure not only has a larger specific surface area, but also can achieve enhanced electromagnetic wave absorption performance by undergoing multiple energy dissipations inside. In addition, the PIP preparation method can make TiO2 evenly dispersed in the matrix and gradually form a dense microstructure, which can not only reduce the diffusion channel of corrosive media inside the material, but also reduce the gaps at the interface, forming a physical barrier on the surface or inside.
[0029] Among them, Yb2Si2O7 is the matrix of the absorbing ceramic, which mainly plays a role in corrosion resistance, and changing the content of the absorbent TiO2 can adjust the dielectric properties of the composite ceramic matrix, so that it has the ability to absorb electromagnetic waves.
[0030] In addition, the present invention also provides the application of the above-mentioned TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix in microwave absorption.
[0031] And, an extension of this application, a microwave absorbing material, the active ingredient of which is the above-mentioned TiO2-based microwave absorbing ceramic with Yb2Si2O7 as the matrix.
[0032] Principle of the present invention:
[0033] The present invention uses a sol-gel method to prepare Yb2Si2O7 powder. First, a pore-forming agent polyvinyl alcohol is mixed into the Yb2Si2O7 powder, and the powder is pressed and calcined at high temperature to obtain porous Yb2Si2O7 ceramics. Then, isopropyl titanate or tetrabutyl titanate is introduced into the porous Yb2Si2O7 ceramics through a polymer impregnation pyrolysis (PIP) method. After solidification and pyrolysis, YbSiOTi composite ceramics are obtained, and a unique composite structure combining flakes and spheres is formed at the microscopic level. The structure has a large specific surface area and is more conducive to various polarization mechanisms such as interface polarization, thereby broadening the electromagnetic wave absorption band. The complexity of the structure enables the electromagnetic wave to undergo multiple reflection, scattering, absorption and other processes inside the material, and the energy is fully lost. Yb2Si2O7 and TiO2 have heterogeneous interfaces, defects and amorphous structures in YbSiOTi ceramics, which is conducive to improving the interface polarization loss and thus enhancing the absorption of electromagnetic waves by YbSiOTi ceramics, that is, the electromagnetic wave absorption performance of YbSiOTi composite ceramics has been significantly improved; not only that, the uniform structure formed by the PIP process is more conducive to maintaining the stability of the material under high temperature and water-oxygen environment than the cold pressing method, and further realizes the controllable adjustment of the electromagnetic wave absorption performance of composite ceramics.
[0034] Polymer impregnation pyrolysis (PIP) process: Through multiple impregnation, curing and pyrolysis cycles, TiO2 is evenly dispersed in the matrix and gradually forms a dense microstructure. This dense structure reduces the diffusion channels of corrosive media (such as water, oxygen, etc.) inside the material, prevents them from contacting the internal components of the material, thereby improving the corrosion resistance of the material; and chemical bonding or strong interaction is formed between TiO2 and the Yb2Si2O7 matrix, reducing defects and voids at the interface. TiO2 can form a physical barrier on the surface or inside the matrix, and when the material is corroded or oxidized, the chemical bonds can resist bond breakage and structural damage caused by external factors, maintaining the chemical integrity of the material.
[0035] The advantages of the present invention are:
[0036] 1. The present invention adopts porous Yb2Si2O7 ceramics with a relatively low dielectric constant as the matrix of the electromagnetic wave absorbing material, controls the content of the absorber by controlling the number of precursor infiltration pyrolysis (PIP) cycles, and prepares YbSiOTi composite phase ceramics with adjustable dielectric constant and electromagnetic wave absorption properties.
[0037] 2. In the present invention, as the content of the absorber (TiO2) increases, the electromagnetic wave dissipation performance of the YbSiOTi ceramic is significantly improved. When the absorber content is 12.5wt%, the YbSiOTi ceramic can absorb 99.99% of the electromagnetic waves.
[0038] 3. The present invention obtains YbSiOTi composite wave absorbing ceramics by repeated impregnation, curing and pyrolysis. The whole operation process is simple and easy to implement, and is suitable for large-scale industrial production and application.
[0039] 4. Compared with the cold pressing method to introduce TiO2nws, the spherical TiO2 introduced by the present invention through the polymer impregnation and cracking method has better dispersion and bonding strength with the matrix, and is also more excellent in maintaining structural stability and mechanical properties at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 SEM images of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2, (a)-(b) PIP-1, (c)-(d) PIP-2, (e)-(f) PIP-3, (g)-(j) EDS images;
[0041] Figure 2 TEM image of nano-YbSiOTi composite ceramics of Example 1;
[0042] Figure 3 This is the Raman spectrum of the nano YbSiOTi composite ceramic of Example 1;
[0043] Figure 4 These are the three-dimensional RL curve and the two-dimensional RL curve of the nano-YbSiOTi composite ceramic in Example 1. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0045] Example 1
[0046] A method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as a matrix, the specific steps are as follows:
[0047] 1) Yb(NO3)3·6H2O was stirred and dissolved in deionized water to obtain solution A, and tetraethyl orthosilicate was stirred and dissolved in ethanol to obtain solution B; at room temperature, solution A was added to solution B and stirred and mixed to obtain gel C, wherein the molar ratio of Yb(NO3)3·6H2O to tetraethyl orthosilicate was 1:1, the concentration of Yb(NO3)3 in solution A was 4 mol / L, and the concentration of tetraethyl orthosilicate in solution B was 4 mol / L; gel C was dried at 90°C for 22 h and at 150°C for 11 h, and then heat-treated at 1200°C for 2 h to obtain powder D; powder D was milled in an agate ball mill for 30 min, and the ball milling was repeated 10 times with an interval of 15 min each time to obtain Yb2Si2O7 powder;
[0048] 2) 3.0 g of Yb2Si2O7 powder and 1 g of polyvinyl alcohol were mixed evenly, and then pressed under a pressure of 20 MPa (30 MPa, 15 min), and sintered in air at a temperature of 1400 ° C for 3 h to obtain porous Yb2Si2O7 ceramics;
[0049] 3) Under vacuum conditions, porous Yb2Si2O7 ceramics were placed in C 16 H 36 The porous Yb2Si2O7 ceramics were immersed in O4Ti solution for 30 minutes, and then placed in an oxygen-free environment at 120℃ for curing for 2 hours, and then placed in an argon environment at 1400℃ for pyrolysis reaction for 2 hours to make the solidified C 16 H 36 O4Ti is pyrolyzed into TiO2;
[0050] 4) The impregnation, curing and cracking process of step 3) was repeated for two more times to finally obtain the YbSiOTi composite ceramic. That is, PIP was performed three times in total in this embodiment, and the product was recorded as P-3.
[0051] Comparative Example 1
[0052] The difference from Example 1 is that after step 3), the corresponding product is obtained and step 4) is no longer performed, that is, only one PIP is performed in this comparative example, and the product is recorded as P-1.
[0053] Comparative Example 2
[0054] The difference from Example 1 is that in step 4), the impregnation, curing and cracking process of step 3) is repeated only once to obtain the corresponding product, that is, PIP is performed twice in this comparative example, and the product is recorded as P-1.
[0055] In order to verify the influence of different PIP times on the product, the present invention makes the following comparison:
[0056] 1. The microstructure of YbSiOTi composite ceramics with different PIP times is as follows: Figure 1 As shown:
[0057] Product P-3: Nano-YbSiOTi composite ceramics present porous properties and flaky structures. TiO2 is spherically distributed in the Yb2Si2O7 matrix. Under an external alternating electromagnetic field, residual defects and heterogeneous interfaces in the composite ceramics will produce polarization losses, enhancing the electromagnetic wave absorption performance.
[0058] Product P-1: It has porous properties and a powdery skeletal structure, with TiO2 distributed in the Yb2Si2O7 matrix in flake form.
[0059] Product P-2: It has porous properties and a powdery skeletal structure, with TiO2 in the form of flakes and spheres distributed in the Yb2Si2O7 matrix.
[0060] With the increase of PIP cycle times, the TiO2 content on the surface of the composite ceramics gradually increases and changes from the initial flake structure to a sphere. Figure 1 (a)-(f) are shown; in order to better analyze the TiO2 structural distribution state in the YbSiOTi composite material of the P-3 sample (PIP times is 3 times), the EDS spectrum is analyzed, and the EDS image is shown Figure 1 As shown in (g)-(j);
[0061] 2. In order to observe the dispersion state, morphology and lattice of TiO2 in the Yb2Si2O7 matrix structure, the TEM image of the ceramic is shown in Figure 2 , (a) is the TEM image of YbSiOTi ceramics, it can be seen that TiO2 is on the surface of the Yb2Si2O7 matrix and separated from each other, (b)-(g) are enlarged views of (a), some new nano-heterogeneous interfaces are formed between TiO2 and the Yb2Si2O7 matrix as shown in (g) (green solid line), the plane spacing of the nanoparticles is 0.24nm and 0.32nm (marked with white solid line and red), corresponding to the (1 0 3) crystal plane of TiO2 and the (0 2 1) crystal plane of Yb2Si2O7, respectively, and some defects marked with purple solid lines are also observed; (e) is an amorphous structure (marked with yellow solid line); from the above analysis, it can be seen that through microscopic observation, it can be found that this heterogeneous interface, defects and amorphous structure exist in YbSiOTi ceramics, and it is beneficial to improve the interface polarization loss, thereby enhancing the absorption of electromagnetic waves by YbSiOTi ceramics;
[0062] 3. Xrd and Xps diagrams of different PIP times are shown in Figure 3 ,With the increase of PIP cycle number, the TiO2 peak of the composite ceramic also increases significantly, as shown in (a). With the change of TiO2 content, the peak intensity of Ti bond in X-ray photoelectron spectroscopy gradually increases, indicating the introduction of TiO2, as shown in (b)-(d).
[0063] 4. The dielectric constant and 3D reflection coefficient of different PIP times at different frequencies are shown in Figure 4 As the content of TiO2 absorber increases, the dielectric constant of the composite ceramic also increases, as shown in (a)-(c). The minimum reflection coefficient (RL) in YT-1 (corresponding to product P-1) and YT-2 (corresponding to product P-2) min) are all greater than -10dB, and no effective absorption bandwidth (EAB) appears as shown in (d)-(e), while in YT-3 (corresponding product P-3), it reaches below -10dB ((f)). That is, compared with P-1 and P-2, the RL of P-3 is min The value reaches -41.2dB at 8.9GHz, indicating that the absorption of electromagnetic waves reaches 99.999%, EAB is 3.4GHz, and the thickness is 2.9mm. It can be seen that the effect of PIP three times is significantly improved compared with one or two times.
[0064] Example 2
[0065] A method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as a matrix, the specific steps are as follows:
[0066] 1) Yb(NO3)3·6H2O was stirred and dissolved in deionized water to obtain solution A, and tetraethyl orthosilicate was stirred and dissolved in ethanol to obtain solution B; at room temperature, solution A was added to solution B and stirred and mixed to obtain gel C, wherein the molar ratio of Yb(NO3)3·6H2O to tetraethyl orthosilicate was 1:1.5, the concentration of Yb(NO3)3 in solution A was 5 mol / L, and the concentration of tetraethyl orthosilicate in solution B was 5 mol / L; gel C was dried at 70°C for 30 h and at 110°C for 13 h, and then heat-treated at 1100°C for 4 h to obtain powder D; powder D was milled in an agate ball mill for 60 min, and the ball milling was repeated 5 times with an interval of 20 min each time to obtain Yb2Si2O7 powder;
[0067] 2) 4.0 g of Yb2Si2O7 powder and 1 g of polyvinyl alcohol were mixed evenly, and then pressed under a pressure of 20 MPa (20 MPa, 30 min), and sintered in air at a temperature of 1600 ° C for 2 h to obtain porous Yb2Si2O7 ceramics;
[0068] 3) Under vacuum conditions, porous Yb2Si2O7 ceramics were placed on C 16 H 36 The porous Yb2Si2O7 ceramics were immersed in O4Ti solution for 60 minutes, and then placed in an oxygen-free environment at 150°C for 2 hours for curing. Then, they were placed in an argon environment at 1500°C for 2 hours for cracking reaction. 16 H 36 O4Ti is pyrolyzed into TiO2;
[0069] 4) Repeat the impregnation, curing and cracking process of step 3) for three more times to finally obtain YbSiOTi composite ceramics.
[0070] Example 3
[0071] A method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as a matrix, the specific steps are as follows:
[0072] 1) Yb(NO3)3·6H2O was stirred and dissolved in deionized water to obtain solution A, and tetraethyl orthosilicate was stirred and dissolved in ethanol to obtain solution B; at room temperature, solution A was added to solution B and stirred and mixed to obtain gel C, wherein the molar ratio of Yb(NO3)3·6H2O to tetraethyl orthosilicate was 1:1.2, the concentration of Yb(NO3)3 in solution A was 3.5 mol / L, and the concentration of tetraethyl orthosilicate in solution B was 3.5 mol / L; gel C was dried at 80°C for 25 h and at 130°C for 12 h, and then heat treated at 1150°C for 3 h to obtain powder D; powder D was milled in an agate ball mill for 20 min, and the ball milling was repeated 15 times with an interval of 10 min each time to obtain Yb2Si2O7 powder;
[0073] 2) 7.0 g of Yb2Si2O7 powder and 1 g of polyvinyl alcohol were mixed evenly, and then pressed under a pressure of 20 MPa (26 MPa, 20 min), and sintered in air at a temperature of 1500°C for 2.5 h to obtain porous Yb2Si2O7 ceramics;
[0074] 3) Under vacuum conditions, porous Yb2Si2O7 ceramics were placed in C 16 H 36 The porous Yb2Si2O7 ceramics were immersed in O4Ti solution for 40 minutes, and then placed in an oxygen-free environment at 100℃ for curing for 3 hours, and then placed in an argon environment at 1200℃ for pyrolysis reaction for 3 hours to make the solidified C 16 H 36 O4Ti is pyrolyzed into TiO2;
[0075] 4) Repeat the impregnation, curing and cracking process of step 3) for 4 more times to finally obtain YbSiOTi composite ceramics.
[0076] Example 4
[0077] The difference from Example 1 is that in step 2), isopropyl titanate solution is used for impregnation.
[0078] The isopropyl titanate solution or tetrabutyl titanate solution used above is a commercially available product with a concentration of more than 99%. For the samples prepared in Examples 2-4, the microscopic morphology is the same as that in Example 1, and they all show porous properties. TiO2 is in a lamellar structure and spherical distribution in the Yb2Si2O7 matrix. Under an external alternating electromagnetic field, the residual defects and heterogeneous interfaces in the composite ceramic will produce polarization losses, enhancing the electromagnetic wave absorption performance. Because Yb2Si2O7 ceramics themselves have high oxidation resistance and corrosion resistance, and after the introduction of TiO2 and PIP treatment, it has good electromagnetic wave absorption performance, which further confirms that the scheme of the present invention can be used in harsh environments, has good environmental adaptability and has excellent performance in absorbing electromagnetic waves.
[0079] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A method for preparing a TiO2-based microwave absorbing ceramic with Yb2Si2O7 as a matrix, characterized in that: 1) Yb2Si2O7 powder and polyvinyl alcohol are mixed uniformly to obtain a mixture, and the mixture is pressed into a shape, and then sintered in an air atmosphere at a temperature of 1400-1600° C. for 2-3 hours to obtain a porous Yb2Si2O7 ceramic; 2) Under vacuum conditions, the porous Yb2Si2O7 ceramic obtained in step 1) is immersed in an isopropyl titanate solution or a tetrabutyl titanate solution for 30-60 minutes, then placed in an oxygen-free environment at a temperature of 100-150° C. for curing for 2-3 hours, and finally placed in an inert atmosphere for pyrolysis, so that the immersed isopropyl titanate solution or tetrabutyl titanate is anaerobic pyrolyzed into TiO2; 3) Repeat step 2) for 2-4 times to finally obtain TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix, namely, nano-YbSiOTi composite microwave absorbing ceramics.
2. The method for preparing the TiO2-based microwave absorbing ceramic with Yb2Si2O7 as the matrix according to claim 1, characterized in that: In step 1), the mass fraction of Yb2Si2O7 powder in the mixture is 70-90%.
3. The method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix according to claim 1 or 2, characterized in that: In step 1), the conditions for compression molding are: 20-30Mpa, 15-30min.
4. The method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix according to claim 3, characterized in that: In step 2), the pyrolysis temperature is 1200-1500° C. and the time is 2-3 hours.
5. The method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix according to claim 4, characterized in that: In step 1), the preparation method of Yb2Si2O7 powder is as follows: Dissolve Yb(NO3)3·6H2O in deionized water to obtain solution A; Dissolve ethyl orthosilicate in ethanol and stir to obtain solution B; At room temperature, solution A and solution B are mixed and stirred to obtain a transparent gel C; After drying gel C, it was calcined, cooled to room temperature, and ball-milled to obtain Yb2Si2O7 powder; The drying process conditions are: first drying at 70-90°C for 20-30h, and then continuing drying at 110-150°C for 11-13h; The process conditions for roasting are: roasting temperature is 1100°-1200°C, and roasting time is 2-4h; The ball milling process is as follows: ball milling for 20-60 minutes, repeating this process 5-15 times with a time interval of 10-20 minutes, and obtaining Yb2Si2O7 powder after drying.
6. The method for preparing TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix according to claim 5, characterized in that: In step 1), the molar ratio of Yb(NO3)3·6H2O to ethyl orthosilicate is 1:1-1.5; The concentration of Yb(NO3)3·6H2O in solution A is 3.5-5 mol / L, and the concentration of ethyl orthosilicate in solution B is 3.5-5 mol / L.
7. A TiO2-based microwave absorbing ceramic with Yb2Si2O7 as the matrix, characterized in that: The product is prepared by the preparation method described in any one of claims 1 to 6.
8. Application of the TiO2-based microwave absorbing ceramics with Yb2Si2O7 as the matrix as claimed in claim 7 in microwave absorption.
9. A wave absorbing material, characterized in that: Its effective component is the TiO2-based microwave absorbing ceramic with Yb2Si2O7 as the matrix as described in claim 7.